(untitled) (Eurasian Research Bulletin, 2024)
The article examines important issues related to the improvement of excise tax administration. Excise tax plays an important role in the formation of state revenues and regulation of consumption of certain goods and services. Analyzes issues and suggests potential solutions to enhance excise tax collection, streamline administrative processes and ensure compliance. By addressing these issues, countries can optimize excise tax revenues and achieve better fiscal and regulatory outcomes.